2022
DOI: 10.3389/fpsyt.2022.986378
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial magnetic stimulation and intravenous ketamine combination therapy for treatment-resistant bipolar depression: A case report

Abstract: About a third of patients suffering from major depression develop treatment-resistant depression (TRD). Although repetitive transcranial magnetic stimulation (rTMS) and intravenous ketamine have proven effective for the management of TRD, many patients remain refractory to treatment. We present the case of a patient suffering from bipolar TRD. The patient was referred to us after failure to respond to first-and second-line pharmacotherapy and psychotherapy. After minimal response to both rTMS and ketamine alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
(42 reference statements)
0
6
0
Order By: Relevance
“…It has been found that the excitatory neurotransmitter glutamate levels are generally reduced in MDD, especially in the prefrontal cortex (Abdallah et al, 2014;Henter et al, 2021;Kantrowitz et al, 2021). Also, glutamate receptor antagonists are more effective in combination with transcranial magnetic therapy for MDD (Best et al, 2019;Elkrief et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that the excitatory neurotransmitter glutamate levels are generally reduced in MDD, especially in the prefrontal cortex (Abdallah et al, 2014;Henter et al, 2021;Kantrowitz et al, 2021). Also, glutamate receptor antagonists are more effective in combination with transcranial magnetic therapy for MDD (Best et al, 2019;Elkrief et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that the excitatory neurotransmitter glutamate levels are generally reduced in MDD, especially in the prefrontal cortex ( Abdallah et al, 2014 ; Henter et al, 2021 ; Kantrowitz et al, 2021 ). Also, glutamate receptor antagonists are more effective in combination with transcranial magnetic therapy for MDD ( Best et al, 2019 ; Elkrief et al, 2022 ). In the present study, we found that the amplitude of P60 in depressed patients was positively correlated with the severity of depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The progress during the ECT and ketamine infusion in our case ( Table 1 and Table 2 ) suggests that ketamine infusion may be less effective than BP-RUL-ECT in patients with TRBPD. In addition to ECT, TMS monotherapy or combination therapy with ketamine infusion may be an option for those who fail ketamine infusion alone, but large studies are needed to validate the results from case reports and small sample studies [ 40 , 41 , 42 ].…”
Section: Clinical Applicationsmentioning
confidence: 99%